The reality of the application of leaders and supervisors in public and private primary schools in Jeddah to indicators of learning outcomes in the light of the supervisory performance leadership system in Saudi schools - Bajabir, Sulafah Salah; Alsaigh, Najat Mohammed Saeed (Journal of Educational and Psychological Sciences, 2023)
The research aims to identify the application level of primary school principals and supervisors of learning outcomes indicators in light of supervisory and school performance leadership system in Central Jeddah Education Office from deputy principals’ point of view, and determination of statistically significant differences between sample members’ average responses to their application by variables (type of education/job title/years of experience). The descriptive approach was used to collect data based on a questionnaire. The research population consisted of all primary school deputy principals in Central Jeddah Education Office government and private schools: of (160). A random sample of (59) deputy was selected. The research reached a number of results, mainly: Application level of primary school principals and supervisors of the effectiveness of basic skills enhancement was (strongly agree); application level of primary school principals and supervisors of the indicators: Evaluation of learning outcomes for academic stages- technical visits of the school principal and educational supervisor- school ranking in qualitative performance of learning outcomes’ remedial actions was (agree). The research identified that there are statistically significant differences between sample members’ responses to the effectiveness of basic skills enhancement indicator attributed to difference in job title variable towards “Student Affairs Deputy” title. There are no statistically significant differences between sample members’ responses to remaining indicators for “Student Affairs Deputy”. There are no statistically significant differences between sample members’ responses to learning outcomes indicators attributed to difference in the variables (type of education/years of experience) and job title variable for (educational affairs deputy/school affairs deputy). The research made several recommendations, mainly: Presenting learning outcome indicators’ results through one platform, consolidating works through which, providing feedback to schools on their students’ performance level, and Ministry of Education’s approval of research results to link learning outcome indicators with the Saudi Arabia 2030 vision’s vital indicators.
Keywords: Leaders; supervisors; learning outcome indicators; supervisory and school performance leadership system; primary schools, government and private